Method of suppressing the multipactoring discharges - Lobzov, L.D.; Shulika, N.G. (Вопросы атомной науки и техники, 2002)
The present paper describes a method of suppressing the multipactoring discharges between electrodes in an accelerating structure of an evacuated resonator of an accelerator. The method consists in synchronous exciting the superposition of radio-frequency electric fields at a resonator operating frequency from two self-excited oscillatory circuits, the parameters of one circuit being independent on the shunt effect of discharges being suppressed. In this method the priority of fields is of equal value with meeting the condition that every of them could ensure the exceeding of the upper discharge range limit of any multipactoring which appears, while another field provides a main contribution into a required level of the operating electric field in the accelerator.